Answer:
x = 1
Step-by-step explanation:
Radical expression:
Let's find the value of x.
Solved:
√(x+3)-1 = x
Transpose -1 to RHS:
Squaring both LHS and RHS,we have:
Subtracting x^2+2x+1 from both sides,we have:
Factoring LHS,we have:
Setting (-x+1) = 0 and (x+2) = 0 each time:
Now
There are two solutions– (1,-2)
Let's plug to the given equation to check.
√(x+3) -1 = x
Equation is true,when plugged to x = 1.
√(x+3) -1 = x
Equation is false,when plugged to x = -2.
Hence,the value of x is 1.
-Regards,Hannah